2021
DOI: 10.1111/eip.13247
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the association between emotional stress reactivity and psychosis

Abstract: Aim Emotional stress reactivity may be a mediating factor in the association between trauma and psychosis. This review aimed to (i) identify, summarise and critically evaluate the link between emotional stress reactivity and psychotic experiences (ii) examine evidence for a 'dose–response' relationship between stress reactivity and psychosis in the wider psychosis phenotype (i.e., sub‐clinical symptoms). Methods Electronic database searches (PsychINFO, MEDLINE, EMBASE) were conducted for studies which investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 111 publications
(132 reference statements)
1
8
0
Order By: Relevance
“…It has previously been found that emotional reactivity to stress may lead to positive symptomatic states in sub‐clinical (Kwapil et al, 2012; Muddle et al, 2021; Pries et al, 2020) and clinical samples (Klippel et al, 2021; So et al, 2018). The current study builds on these findings by identifying attachment avoidance, not anxiety, as a possible maintaining factor to stress reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been found that emotional reactivity to stress may lead to positive symptomatic states in sub‐clinical (Kwapil et al, 2012; Muddle et al, 2021; Pries et al, 2020) and clinical samples (Klippel et al, 2021; So et al, 2018). The current study builds on these findings by identifying attachment avoidance, not anxiety, as a possible maintaining factor to stress reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…( 8 ) suggested that the level of vulnerability to psychosis mirrored the level of emotional stress reactivity. Taken together, emotional stress sensitivity (i.e., reactivity and recovery) has been shown to be an important mechanism in the pathway to psychosis ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various studies have reported that anxiety and emotional dysregulation are associated with poorer prognoses for high-risk patients (7,8). Specifically, reduced tolerance to daily life stress has been represented a critical symptom that mediates the transition of patients to psychosis (9)(10)(11)(12)(13). Still, the neurobiological mechanisms underlying the link between stress and psychosis vulnerability remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%